2014
DOI: 10.1016/j.ancv.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome pós‐trombótica e qualidade de vida em doentes com trombose venosa ilio‐femoral

Abstract: Recebido a 4 de julho de 2014; aceite a 10 de setembro de 2014 Disponível na Internet a 23 de outubro de 2014 PALAVRAS-CHAVETrombose venosa ilio-femoral; Trombólise dirigida por cateter; Qualidade de vida Resumo Objetivo: Caraterizar o síndrome pós-trombótico e a qualidade de vida em doentes com antecedentes de trombose venosa profunda (TVP) ilio-femoral, possíveis candidatos a trombólise dirigida por cateter na altura do diagnóstico. Material e métodos: Revisão retrospetiva dos processos clínicos dos doentes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…In addition, post-thrombotic syndrome occurs as an important complication of the disease, which appears in up to 50% of patients with DVT. This syndrome is characterized by the chronicity of the symptoms of the disease and is diagnosed from the sum of signs (pre-tibial edema, hyperpigmentation, erythema, venous ectasia) and symptoms (cramps, pain, heaviness, pruritus), by the scale of Villalta (Charlo, et al, 2020;Brazilian Society of Angiology, 2015;Brandão, et al, 2018;Maia, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, post-thrombotic syndrome occurs as an important complication of the disease, which appears in up to 50% of patients with DVT. This syndrome is characterized by the chronicity of the symptoms of the disease and is diagnosed from the sum of signs (pre-tibial edema, hyperpigmentation, erythema, venous ectasia) and symptoms (cramps, pain, heaviness, pruritus), by the scale of Villalta (Charlo, et al, 2020;Brazilian Society of Angiology, 2015;Brandão, et al, 2018;Maia, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1 Notwithstanding, these results are lower than those previously reported in a Portuguese retrospective cohort study, where PTS was found in 89.3%. 26 This study included 39 patients with ilio-femoral DVT who were potential candidates for catheter-directed thrombolysis at the time of diagnosis. 27 The inclusion of DVTs restricted to those affecting the ilio-femoral sector may underlie the disparity in PTS incidence since ilio-femoral DVT is often associated with higher rates of PTS.…”
Section: Discussionmentioning
confidence: 99%
“…Com complicações potencialmente fatais 5 , as manifestações clínicas variam de acordo com a gravidade do caso 6 . A cavidade cardíaca e artéria aorta dificilmente são obstruídas pelos trombos, devido ao grande calibre e rápido fluxo sanguíneo da região.…”
unclassified